Hemostasis with emergently modified application of intra‐aortic balloon occlusion in a patient with impending cardiac arrest following blunt proximal thigh amputation. Issue 1 (14th July 2014) - Uchida, Kotaro; Homma, Hiroshi; Oda, Jun; Yukioka, Tetsuo; Nagai, Noriko; Mishima, Shiro; Ohta, Shoichi
Abstract : Case: A 30‐year‐old woman had her left thigh run over by a train. We tried to compress the left femoral area to control the arterial bleeding, but bleeding continued from the stump and injured soft tissue. The application of a tourniquet bandage also failed because of the limited remaining thigh. She developed impending cardiac arrest. As the left femoral arterial pulsation was still palpable, we inserted an intra‐aortic balloon occlusion catheter percutaneously. The hemorrhage from the stump region decreased rapidly. She was transferred to an operating room to carry out surgical hemostasis, and it was confirmed with deflation of the balloon in the common iliac artery. Outcome: There was no complication of the skin or soft tissue at the surgical site caused by impaired circulation, and her consciousness fully recovered. Conclusion: We report the successful control of bleeding by the emergently modified application of intra‐aortic balloon occlusion in the left common iliac artery.